2019
DOI: 10.3390/m1093
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-((1,4-Dimethoxy-1,4-dioxobutane-2,3-diylidene)bis(azanylylidene))bis(quinoline-3-carboxylic acid)

Abstract: The title compound, 2,2 -((1,4-dimethoxy-1,4-dioxobutane-2,3-diylidene)bis(azanylylidene)) bis(quinoline-3-carboxylic acid) was synthesized from isoxazolo[3,4-b]quinolin-3(1H)-one and dimethyl acetylenedicarboxylate (DMAD) via a double aza-Michael addition followed by [1,3]-H shifts. The product was characterized by infrared and nuclear magnetic resonance spectroscopy, as well as elemental analysis and high-resolution mass spectrometry (HRMS). The proposed reaction mechanism was rationalized by density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The authors reported the synthesis of a bis-quinoline carboxylic acid derived from the corresponding isoxazolo-quinoline and dimethyl acetylenedicarboxylate (DMAD) under mild alkaline conditions. DFT calculations revealed that the product was more favorable than the double Michael addition isoxazolone product, which according to the proposed by the authors' mechanism, is formed as an intermediate [5].…”
mentioning
confidence: 76%
“…The authors reported the synthesis of a bis-quinoline carboxylic acid derived from the corresponding isoxazolo-quinoline and dimethyl acetylenedicarboxylate (DMAD) under mild alkaline conditions. DFT calculations revealed that the product was more favorable than the double Michael addition isoxazolone product, which according to the proposed by the authors' mechanism, is formed as an intermediate [5].…”
mentioning
confidence: 76%